Spinal meningioma surgery: predictive factors of outcome - SUBAČIŪTĖ, Jadvyga (Acta medica Lituanica, 2010)
Object. The aim of this report is to evaluate the predictive factors of poor functional outcome in spinal cord meningioma surgery. Materials and methods. One hundred patients with spinal cord meningioma (14 men and 86 women at the age of 13–87) operated in our Neurosurgical Clinic were analyzed. Statistical data analysis evaluated the importance of symptoms, duration and neurological status before surgery and meningioma localization according to the spinal cord axis for the results of surgery. Results. Total tumour removal was achieved in 92 and subtotal in 8 cases. In the early postoperative period, 61% of patients recovered and improved. The results of surgery reliably depended on the duration of symptoms before operation (p = 0.05). The risk of unimprovement prevailed in patients with paraplegia in comparison with other motor deficits. The risk of poor outcome increased with a 95% confidence index when tumour localization was ventral and caudal as compared with the dumbbell, dorsal and epidural localization taken together. Mortality was 3% after the subtotal removal of tumour, and in 3% of cases neoplasma recurred. The mean follow up was 1–22 years. The outcome at the last followup was good in 50% of cases. Conclusions. Functional outcome after surgery reliably dependeds on: 1) the duration of symptoms before hospitalization (with a poor outcome when the duration of illness was more than 3 years); 2) the preoperative neurological condition of patients (a poor prognosis in paraplegic patients); 3) tumour localization with respect to the spinal cord axis (risk of unimprovement when the tumour was of ventral and caudal localization). Keywords: meningioma of spinal cord, surgery, outcome, predictive factors, late prognosis